(untitled) (Annals of Medical Research, 2021)
Aim: To investigate whether dynamic contrast enhanced perfusion T1-weighted (DCE T1-W) three-dimensional volume interpolated breath-hold examination (3-D vibe) contributes to perianal fistula staging.Materials and Methods: A total of 110 patients who underwent pelvic magnetic resonance imaging (MRI) (1,5 tesla, Siemens, Avanto) with the preliminary diagnosis of perianal fistula were included in our retrospective study. In our perianal fistula MRI protocol, DCE T1-W 3D vibe sequence was in axial plane with fat-saturation and in five phases (precontrast phase and then in the 45th, 60th, 180th and 240th seconds after intravenous contrast administration). Perianal fistula staging was performed according to T2-weighted sequence findings (acute, subacute, chronic) and by clinical history. Semi-quantitative measurements of the perianal fistula were made with the ROIs placed on the perianal fistula and left femoral artery. Then measurements were made as follows: Type of contrast curve obtained, staining peak time and slope angle of the curve. All measurements were performed independently by two radiologists at different times. Interobserver agreement was also evaluated (Cohen’s kappa).Results: The phases of reaching the peak time (TTP) of contrast increases as the perianal fistula stage increases (mean phases of TTP values were 2.2 th± 1.2 in acute phase fistulas, 2.8 th ± 1.2 in subacute perianal fistulas; 4.4 th ± 1 in chronic fistulas). The angle of inclination decreased as the stage of the perianal fistula increased (42.2 ± 13.2 degrees; 27 ± 11.3 degrees and 9.6 ± 2.3 degrees, respectively).Conclusion: Diagnosis of perianal fistula with physical examination can be confusing. Sometimes there can be fistulas with different stages in the same patient. Therefore, the use of IV contrast-enhanced pelvic examination with dynamic technique may provide information about the perianal fistula stage.